The Differences of Anxiety of Pregnant Women in Trimester III on Lavender Aromatherapy - Agnes Purba; Netti Meilani Simanjuntak; Rinawati Sembiring (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Childbirth can sometimes cause anxiety in pregnant women, especially in the third trimester. Pregnant women are worried about whether the baby is normal or not, the pain that will be felt and the delivery is normal or not. In order to facilitate pregnant women to go through their anxiety without complications, there are currently many being given care using lavender aromatherapy. Lavender contains substances that relax pregnant women, thereby eliminating anxiety. An initial survey conducted at PMB Erni Atika Sari, there were 19 pregnant women who said that they had anxiety in the third trimester of pregnancy, especially in the face of childbirth. Therefore, this study was conducted to determine the effect of lavender aromatherapy on the anxiety of pregnant women in the third trimester. This research was conducted with a quasi-experimental design with a non-equivalent control group design. The research location is PMB Erni Atika Sari and PMB Lismawati. The sample is primigravida third trimester pregnant women with saturated sampling with a total of 40 people. The results showed that there was an effect of giving lavender aromatherapy on the anxiety of primigravida pregnant women in the third trimester (p = 0.000). For this reason, it is expected that pregnant women can use lavender therapy as a complementary therapy that provides a relaxing effect so that it can reduce the anxiety of pregnant women facing childbirth.